The level of intelligence relationship kinetic response in obese children, ages (7-9 years) - يعرب عبد الباقي; حيدر مهدي عبد الصاحب (College of Physical Education and Sport Sciences, 2019)
The skill of beating overwhelming is the most important of those attacking skills that must be accessed by a very advanced stage of the stages of learning, manifested us the importance of research in the study and assess the level of motion mechanism with national team players Iraqi volleyball using science biomchanic as a way to evaluate so that we can determine the level of similarity locomotor performance of members of the sample and thus giving the perception of what the nature of motor performance , as is the research in this area of service for each players and coaches alike. As the research aims to assess the level of performance of the mechanism beating overwhelming higher skill through some of the variables biomchanic with national team players Iraqi volleyball . The researchers ended up to a total of the most important conclusions : 1. achieved the members of the research sample similar values for each of the variables of the maximum flexion angle of the knee joint of the man left during the jump, as well as in variable distance jump, which means that there are stable in the quality of the performance stage Althmadah beaten overwhelming higher for per player , and the mechanism of learning . 2. achieved the members of the research sample similar values for each of the variable maximum flexion angle of the right leg for a moment of payment as well as in variable maximum flexion angle of the hip moment of payment , which means that there are stable in the quality of the performance stage Alnhi beaten overwhelming higher for per player , and the mechanism of learning